Exposure to Parenting by Lying in Childhood: Associations with Negative Outcomes in Adulthood - Santos, Rachel M.; Zanette, Sarah; Kwok, Shiu M.; Heyman, Gail D.; Lee, Kang (Frontiers in Psychology, 2017)
Parents around the world engage in the practice of parenting by lying, which entails lying to manipulate children’s emotional states and behavior. The current study is the first to examine whether exposure to parenting by lying in childhood is associated with later dishonesty and psychosocial maladjustment in adulthood. Female undergraduate adults retrospectively reported their experiences of parenting by lying during childhood, the current frequency at which they lie to their parents, and their current psychosocial functioning. We found that adults who recalled relatively high levels of parenting by lying during childhood both lie to their parents more often and experience greater psychosocial adjustments problems in adulthood than adults who recalled relatively low levels of parenting by lying during childhood. This study is the first to suggest that parenting by lying during childhood may be associated with negative moral and social outcomes later in life.